Personal demands and job stress through workaholism in the era of digital business - Mirzani Ahmad; Anindya Ardiansari (Jurnal Mantik, 2026)
This study examined the role of personal demands in shaping job stress through workaholism within a digital business ecosystem. The transformation of organizational systems toward platform-based work, real-time performance monitoring, and application-based targets had restructured job demands and intensified performance pressures on employees. In this context, perfectionism and narcissistic tendencies were expected to influence compulsive work behavior and psychological strain. A quantitative approach was employed using survey data collected from employees working in digitally managed organizational environments. The constructs of self-oriented perfectionism, socially prescribed perfectionism, narcissistic tendencies, workaholism, and job stress were measured using standardized instruments, and the data were analyzed using structural equation modeling to test both direct and indirect relationships among the variables. The results indicated that personal demands had significant positive effects on workaholism, which in turn had a significant positive effect on job stress. Workaholism mediated the relationships between personal demands and job stress. The findings suggested that job stress in digital business contexts resulted from the interaction between personal demands and digitally designed work systems